2004
DOI: 10.1111/j.1083-4389.2004.00223.x
|View full text |Cite
|
Sign up to set email alerts
|

Lower Prevalence of Helicobacter pylori Infection in Patients With Inflammatory Bowel Disease But Not With Chronic Obstructive Pulmonary Disease – Antibiotic Use in the History Does Not Play a Significant Role

Abstract: The prevalence of H. pylori compared to the age-matched controls is significantly lower in patients with inflammatory bowel disease but not in those with chronic obstructive pulmonary disease. Antibiotic use is not responsible for the lower prevalence of H. pylori infection in patients with inflammatory bowel disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 12 publications
1
38
2
2
Order By: Relevance
“…However, neither salazopyrine nor the other 5-ASA dr ugs used in IBD reach the concentrations required in the corpus and antrum of the stomach to effect H pylori eradication. In addition, studies of IBD patients and disease control groups including patients with COPD [28] , indicate that the H pylori rates in those individuals exposed to multiple antibiotics are in fact higher compared to those exposed to either no antibiotics or fewer courses.…”
Section: H Pylori Exposurementioning
confidence: 99%
“…However, neither salazopyrine nor the other 5-ASA dr ugs used in IBD reach the concentrations required in the corpus and antrum of the stomach to effect H pylori eradication. In addition, studies of IBD patients and disease control groups including patients with COPD [28] , indicate that the H pylori rates in those individuals exposed to multiple antibiotics are in fact higher compared to those exposed to either no antibiotics or fewer courses.…”
Section: H Pylori Exposurementioning
confidence: 99%
“…Several of these later studies further substituted H. pylori serum IgG or IgA serology for the C 13 urea breath test, an accurate test for assessing active (as opposed to past) infection. These studies also unequivocally confirmed a lower prevalence of H. pylori in IBD patients [66,67,68]. Although all early studies were conducted on European populations, in which IBDs are much more common than in other geographical areas of the world, several more recent studies have confirmed the same trends in Asian and American populations [69,70,71].…”
Section: Epidemiological Evidence Suggests An Inverse Association Betmentioning
confidence: 73%
“…The relatively low risk of H. pylori colonization in IBD patients was initially attributed to the previous exposure to antibiotics such as sulfasalazine [63,65]. As the spontaneous eradication of H. pylori through the use of antibiotics was indeed a possible confounding factor in the early studies - IBD patients are commonly treated with broad-spectrum antibiotics - control groups that had also received antibiotic treatment for conditions such as COPD, and IBD patients that had been treated exclusively with drugs other than antibiotics, were enrolled in several later, more sophisticated studies [66,67]. Such studies with carefully selected control groups confirmed the lower prevalence of H. pylori infection in IBD patients, irrespective of the treatments they received [66,67].…”
Section: Epidemiological Evidence Suggests An Inverse Association Betmentioning
confidence: 99%
See 1 more Smart Citation
“…Pronai et al compared the HP infection rate between CD patients and chronic obstructive pulmonary disease (COPD) patients in two agematched control groups to evaluate the prevalence of HP infection and the influence of antibiotics in these patients. They found that the prevalence of HP infection was lower than that in the control group and that the administration of antibiotics did not affect the HP infection rate [47]. Thus far, the relationship between CD and HP remains controversial, and further study is needed to analyze the issue.…”
Section: Gastric Lesionsmentioning
confidence: 99%